Flexible Graphene Solution‐Gated Field‐Effect Transistors: Efficient Transducers for Micro‐Electrocorticography. (13th November 2017) - Hébert, Clement; Masvidal‐Codina, Eduard; Suarez‐Perez, Alejandro; Calia, Andrea Bonaccini; Piret, Gaelle; Garcia‐Cortadella, Ramon; Illa, Xavi; Del Corro Garcia, Elena; De la Cruz Sanchez, Jose M.; Casals, Damia Viana; Prats‐Alfonso, Elisabet; Bousquet, Jessica; et al.
Abstract: Brain–computer interfaces and neural prostheses based on the detection of electrocorticography (ECoG) signals are rapidly growing fields of research. Several technologies are currently competing to be the first to reach the market; however, none of them fulfill yet all the requirements of the ideal interface with neurons. Thanks to its biocompatibility, low dimensionality, mechanical flexibility, and electronic properties, graphene is one of the most promising material candidates for neural interfacing. After discussing the operation of graphene solution‐gated field‐effect transistors (SGFET) and characterizing their performance in saline solution, it is reported here that this technology is suitable for μ‐ECoG recordings through studies of spontaneous slow‐wave activity, sensory‐evoked responses on the visual and auditory cortices, and synchronous activity in a rat model of epilepsy. An in‐depth comparison of the signal‐to‐noise ratio of graphene SGFETs with that of platinum black electrodes confirms that graphene SGFET technology is approaching the performance of state‐of‐the art neural technologies. Abstract : Flexible graphene solution‐gated field‐effect transistors are proposed as a new advanced technology for neural recordings thanks to the outstanding properties of single‐layer graphene. In this paper, the key concepts of this technology are discussed and its perfect suitability for μ‐ECoG applications is shown by demonstrating the recording of sensory‐evoked potential as well as synchronous activity.